The Role of Family Education in Forming The Iindependent Character of Students in Elementary School - Handayani, Rekno; Purbasari, Imaniar; Setiawan, Deka; Ahmadi, Farid; Praswanti, Ramadhani Putri (International Journal of Elementary Education, 2021)
The character value of elementary school students' independence is one of the problems that becomes a problem for students. The formation of the character value for independence is not only a school task, but the role of the family is also expected to form a character of independence. The purpose of this study was to analyze in depth the role of family education in shaping the independent character values syudents of class IV elementary school. Independence becomes a character value that must be embedded in students, so that independence becomes one of the attitudes needed in the implementation of learning. Descriptive qualitative is the method used in conducting research. The informants used as data sources included parents, students of class IV elementary school, and also class teachers. The techniques used in collecting data include observation, interviews, and documentation. The data analysis used was Milles Huberman's interactive model. The results showed that good family education has a positive role in the formation of the character values for the independence students of class IV elementary school. This can be seen from the independent attitude shown by students both in the family and school environment. Through good family education such as habituation that reflects independence will shape student character. The positive impact of instilling the value of independence is that students are able to fully participate in the learning process at school. The benefits that can be conveyed from the results of the research should be for parents to be able to apply proper family education to elementary school age children, because this education will have a positive impact on children.